1997
DOI: 10.2307/2446018
|View full text |Cite
|
Sign up to set email alerts
|

Fly pollination of Gorteria diffusa (Asteraceae), and a possible mimetic function for dark spots on the capitulum

Abstract: We investigated the functional significance of raised black spots on the ray florets of Gorteria diffusa (Asteraceae) in South Africa. Field observations showed that G. diffusa is pollinated by a small bee-fly, Megapalpus nitidus (Bombyliidae), which is strikingly similar to the raised spots that occur on some of the ray florets. Removal of the spots resulted in a significant decrease in the rate of fly visits to capitula, but did not significantly affect seed set. Replacement of the spots with simple ink spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
93
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 12 publications
1
93
0
1
Order By: Relevance
“…Experiments have established the functional significance of convergent floral traits in several specialized pollination systems in southern Africa. Floral advertising traits, which have been shown by means of manipulative experiments to be functionally important for pollinator attraction, include convergent yellow or orange coloration and dark central markings of flowers pollinated by hopliine beetles (Van Kleunen et al 2007), dark raised spots typically found on flowers pollinated by Megapalpus bee-flies (Johnson & Midgley 1997), the size and red colour of flowers pollinated by Aeropetes butterflies (Johnson & Bond 1994) and the scent of flowers pollinated by spider-hunting wasps (Shuttleworth & Johnson 2009). …”
Section: Pollination Systems As Nichesmentioning
confidence: 99%
“…Experiments have established the functional significance of convergent floral traits in several specialized pollination systems in southern Africa. Floral advertising traits, which have been shown by means of manipulative experiments to be functionally important for pollinator attraction, include convergent yellow or orange coloration and dark central markings of flowers pollinated by hopliine beetles (Van Kleunen et al 2007), dark raised spots typically found on flowers pollinated by Megapalpus bee-flies (Johnson & Midgley 1997), the size and red colour of flowers pollinated by Aeropetes butterflies (Johnson & Bond 1994) and the scent of flowers pollinated by spider-hunting wasps (Shuttleworth & Johnson 2009). …”
Section: Pollination Systems As Nichesmentioning
confidence: 99%
“…Johnson and Midgley (1997) found that flowers of Gorteria diffusa have spots on the ray florets, which are strikingly similar to its pollinator, a small bee‐fly, Megapalpus nitidus (Bombyliidae). These flies are attracted to the spot and try to copulate with it, leading to the conclusion that the dark spots imitate flies to attract males looking for mating (Johnson & Midgley, 1997). The wide distribution of plants with a dark‐center pattern and the recorded behavior of pollinators attracted to these patterns suggest that dark flower center has an adaptive role in pollination.…”
Section: Introductionmentioning
confidence: 99%
“…The system is characterized by variation in floral colour and the complexity and distribution of the black anthocyanin spots at the base of the ray florets (figure 1). These spots, which are complex phenotypic structures, play an important role in the attraction of the bee fly, Megapalpus capensis Wiedeman [30]. M. capensis is the main pollinator of all forms of G. diffusa [28].…”
Section: Introductionmentioning
confidence: 99%